Necklace featuring Radha dancing with Krishna - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli woman’s necklace features Radha dancing with Krishna (left) and Vithoba (a form of Lord Vishnu) with his consort Rakhumai (right). In Maharashtra, Vithoba is also known as Vitthala, Panduranga, Pandharinath, Hari, and Narayan. Rakhumai, also known as Rukmini, is an incarnation of the Goddess Lakshmi.